Answer:
D. 4
Step-by-step explanation:
x=2, y=4 on the graph
Therefore, f(2)=4
~
Hope this helps!
Answer:
14
Step-by-step explanation:
5(x−6+3x)2−6
10(4x-6)-6
40x-60-6
40x-66
x=2
40*2-66
80-66
14
I'm for sure know that it is function is linear but i would wait for others to answer also
Answer:
See explanation, and ask for more details if unclear!
Step-by-step explanation:
The perfect square of this equation is
, since the square would be
. 1/4=4/16, meaning that you can set up the equation in the following way:
![(x^2-x+\frac{1}{4})-\frac{1}{16}=0](https://tex.z-dn.net/?f=%28x%5E2-x%2B%5Cfrac%7B1%7D%7B4%7D%29-%5Cfrac%7B1%7D%7B16%7D%3D0)
![(x-\frac{1}{2})^2=\frac{1}{16}](https://tex.z-dn.net/?f=%28x-%5Cfrac%7B1%7D%7B2%7D%29%5E2%3D%5Cfrac%7B1%7D%7B16%7D)
Take the square root of both sides:
![x-\frac{1}{2}=\pm \frac{1}{4}](https://tex.z-dn.net/?f=x-%5Cfrac%7B1%7D%7B2%7D%3D%5Cpm%20%5Cfrac%7B1%7D%7B4%7D)
Add 1/2 to both sides:
. Hope this helps!
Answer:
there was not enough information provided because Maddison does not know what the original size is.
Step-by-step explanation: